Math, asked by rbrohan4190, 1 year ago

Sec theta ( 1 - sin theta ) (sec theta + tan theta ) = 1

Answers

Answered by utopian08
109

Answer:

multiply first bracket by sec thita

Step-by-step explanation:

for more details find the attatched file

Attachments:
Answered by NirmalPandya
0

Complete question: Prove that sec\theta(1-sin \theta)(sec\theta+tan\theta)=1.

Given,

An expression: sec\theta(1-sin \theta)(sec\theta+tan\theta).

To Find,

We need to prove that sec\theta(1-sin \theta)(sec\theta+tan\theta)=1.

Solution,

The proof of the given statement is as follows -

We need to simplify the expression.

sec\theta(1-sin \theta)(sec\theta+tan\theta)

=(sec\theta-sec\theta  *sin\theta)(sec\theta +tan\theta)

=(sec\theta - \frac{1}{cos\theta}*sin\theta } }) (sec\theta+tan\theta)

=(sec\theta-tan\theta)(Sec \theta+tan\theta ) [Since \frac{sin \theta}{cos \theta}=tan\theta ]

=(sec^2\theta - tan^2\theta)=1   [We know that (a+b)(a-b)=(a^2-b^2)]

Hence, the statement is proved.

#SPJ3

Similar questions